The actions of ryanodine on Ca2+-activated conductances in rat cultured DRG neurones; evidence for Ca2+-induced Ca2+ release - Ayar, Ahmet; Scott, Roderick H. (Springer Verlag, 1999)
The whole-cell recording technique was used to investigate the actions of a calcium release channel ligand, ryanodine, on calcium-activated chloride conductances, and to evaluate ryanodine-sensitive Ca2+-induced Ca2+ release from intracellular stores in cultured neonatal rat DRG neurones. The aim of the project was to use ryanodine as a pharmacological tool to evaluate calcium-induced calcium release in the cell bodies of cultured DRG neurones. Action potential after-depolarizations were attenuated by extracellular application of the chloride channel blocker, niflumic acid (10 ?M), and by ryanodine (10 ?M); these actions occurred without concurrent changes in evoked action potentials. Ryanodine and caffeine (10 mM) activated calcium- dependent conductances and the responses to ryanodine were attenuated by depletion of caffeine-sensitive Ca2+ stores. The current clamp data were complicated by changes in potassium conductances so studies were carried out under voltage clamp and voltage-activated calcium currents and calcium- activated chloride and non-selective cation currents were isolated pharmacologically. Ryanodine (10 ?M) evoked delayed, inward, calcium- activated non-selective cation and chloride currents which reversed close to 0 mV and were attenuated by N-methyl-D-glucamine, niflumic acid and dantrolene. Consistent with actions on action potential after- depolarizations, niflumic acid (10 ?M) and ryanodine (10 ?M) attenuated calcium-activated chloride currents evoked by calcium entry through voltage- activated calcium channels. Niflumic acid and ryanodine had no effects on voltage-activated calcium currents evoked from a holding potential of -90 mV by voltage step commands to 0 mV. In conclusion calcium-activated chloride conductances appear to be activated in part by calcium released from ryanodine-sensitive stores, and significant calcium-induced calcium release may occur locally in cell bodies of DRG neurones as a result of calcium entry through voltage-activated channels during an action potential.
Keywords: Action potential after-depolarizations; Calcium-activated chloride currents; CICR; Cultured sensory neurones; Dantrolene; Niflumic acid; Ryanodine